Cover Picture: Tuning of the open‐circuit voltage by wide band‐gap absorber and doped layers in thin film silicon solar cells (Phys. Status Solidi RRL 8/2015). Issue 8 (August 2015) - Wang, Shuo; Smirnov, Vladimir; Chen, Tao; Zhang, Xiaodan; Xiong, Shaozhen; Zhao, Ying; Finger, Friedhelm
<x xml:space="preserve">Abstract</x> No abstract is available for this article.